Corona Virus Damages The Feel of Worship and Educational Activities for The Community Bagik Lonjer Village, Rensing Sakra Barat: (Beginning of Covid 19 Ramadhan 1442 H) - Hakim, Abdul Azizul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Covid 19 ruined the feel of my Ramadan Worship to be gloomy. On March 17, 2020, which coincided with the graduation of STKIP Harapan Bima students, they were exposed to government announcements regarding the lockdown in each region in Indonesia, which we previously heard from the president of the Republic of Indonesia if the corona virus that hit neighboring countries would not reach Indonesia. This announcement rings in the ears of the corona virus pandemic that exists in this country, it won't last long. In my opinion, it turns out that this virus has ruined all the plans that have crossed our minds since the end of 2019. The unfortunate thing that happened in all of these plans was with the presence of corona which we didn't or wanted to arrive. -Suddenly attacked and paralyzed my country, especially the NTB area.